Versatility of Homogeneous Time-Resolved Fluorescence Resonance Energy Transfer Assays for Biologics Drug Discovery. (April 2015) - Rossant, Christine J.; Matthews, Carl; Neal, Frances; Colley, Caroline; Gardener, Matthew J.; Vaughan, Tristan
Identification of potential lead antibodies in the drug discovery process requires the use of assays that not only measure binding of the antibody to the target molecule but assess a wide range of other characteristics. These include affinity ranking, measurement of their ability to inhibit relevant protein-protein interactions, assessment of their selectivity for the target protein, and determination of their species cross-reactivity profiles to support in vivo studies. Time-resolved fluorescence resonance energy transfer is a technology that offers the flexibility for development of such assays, through the availability of donor and acceptor fluorophore-conjugated reagents for detection of multiple tags or fusion proteins. The time-resolved component of the technology reduces potential assay interference, allowing screening of a range of different crude sample types derived from the bacterial or mammalian cell expression systems often used for antibody discovery projects. Here we describe the successful application of this technology across multiple projects targeting soluble proteins and demonstrate how it has provided key information for the isolation of potential therapeutic antibodies with the desired activity profile.